The inclusion of pregnant women in research during disease outbreaks globally: A scoping review - Haley Kartchner Williams; Maria Docal; Angela Chang Chiu; Catherine Ling; Nancy R Reynolds (Revista Latino-Americana de Enfermagem)
Objective: this scoping review aims to search the literature about conducting research on pregnant women during outbreaks globally and synthesize the findings to identify themes, analyze knowledge gaps, and provide evidence-based recommendations to inform future research. Method: a comprehensive literature search was conducted in November 2023 using PubMed, Embase, CINAHL, Web of Science, Scopus, and Global Health databases. Key terms included “pregnancy,” “disease outbreaks,” “biomedical research,” and “eligibility criteria.” Twenty-three articles published between 2017 and 2023 were included in the synthesis. Results: this review identified a pattern of exclusion of pregnant women from research during multiple disease outbreaks across diverse regions. The exclusion rates ranged from 52% to 97.8%. Ethical and moral concerns were raised, emphasizing the need for a shift toward the presumptive inclusion of pregnant women in research. Recommendations emerged from discussions on the risks and benefits of research participation, global institutional and strategic changes, and the standardized collection of pregnancy-specific data to inform public health responses. Conclusion: this scoping review highlights the systemic exclusion of pregnant women from research during disease outbreaks, underscoring ethical concerns, critical knowledge gaps, and structural barriers while providing a foundation for advancing maternal health research during public health emergencies.